The Influence of Health Education Using Brainstorming Method About Exclusive Breastfeeding on Breastfeeding Mother's Knowledge in PMB D Bogor District in 2023 - Azizah, Zulfa Nur; Noviana, Ekki; Munah, Fauzul (Riviera Publishing, 2024)
Health education is expected to increase the knowledge of breastfeeding mothers in exclusive breastfeeding. West Java Health Profile in 2017 the coverage of exclusive breastfeeding in Bogor Regency was 22.84%. Mother's knowledge can influence exclusive breastfeeding. To determine the effect of health education using the brainstorming method about exclusive breastfeeding on the knowledge of breastfeeding mothers at PMB D Bogor Regency in 2023. This study used a one group pre-test post-test pre-experimental research design. Analytical research method with cross sectional design. Total population of 35 people with a sample of 32 people. The sampling technique used was purposive sampling, and bivariate data analysis used the assisted t-test. The results of the univariate analysis showed that the respondents were aged 20-35 years (84.4%), high school (78.1%), housewife (90.6%), the knowledge of breastfeeding mothers before being given health education using the brainstorming method was mostly lacking (43.8%), the knowledge of breastfeeding mothers after being given health education using the brainstorming method was mostly good (65.6%). The results of the bivariate analysis showed that there was an effect of health education using the brainstorming method about exclusive breastfeeding on increasing the knowledge of breastfeeding mothers with a p-value of 0.000 <0.05. There is an effect of health education using the brainstorming method about exclusive breastfeeding on increasing the knowledge of breastfeeding mothers.